2006
DOI: 10.1159/000094972
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits in Familial Alzheimer’s Disease Associated with M239V Mutation of Presenilin 2

Abstract: The neuropsychological assessment of non-demented subjects with gene mutation of familial Alzheimer’s disease (AD) provides a model for exploring the early cognitive features of the disease. We evaluated 1 patient and 6 non-demented subjects belonging to a family with AD with M239V mutation of the presenilin 2 gene, aiming to verify the contribution of specific cognitive patterns to the characterization of familial AD. One patient, 3 non-demented subjects with M239V mutation and 3 subjects without mutation fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…In addition, the clinical phenotypes of carriers of the M239V mutation varied widely. Our findings, together with previous reports, further suggest that phenotypic heterogeneity exists even at the same codon site because of different amino acid transversions 30 , 32 , 33 .…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the clinical phenotypes of carriers of the M239V mutation varied widely. Our findings, together with previous reports, further suggest that phenotypic heterogeneity exists even at the same codon site because of different amino acid transversions 30 , 32 , 33 .…”
Section: Discussionsupporting
confidence: 86%
“…Memory was relatively spared. Only one study found anosognosia, severe visuospatial impairment, apraxia and fluent aphasia, with relative sparing of memory function in a patient with a known preseniline 2 mutation (M239V) 35 . More clinicopathological studies are necessary to determine whether this combination of symptoms represents a clinical subtype of AD or whether other underlying pathology is responsible for this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Only 7 of these mutations are well documented to be pathogenic, although pathogenicity in several others remains possible. A previous study in an Italian family has identified a distinctive pattern of visuospatial, praxis and language impairments in AD associated with the M239V mutation of the PSEN2 gene [18]. In Japanese patients, epidemiologic and genetic studies of Alzheimer's dementia did not find any mutations in PSEN2 and PSEN1 [19].…”
Section: Discussionmentioning
confidence: 99%